The Role of Educational Management in Shaping National Education Policies in Nigeria: A Critical Review (UNIZIK Journal of Educational Management and Policy, 2024)
Educational management plays a crucial role in the development and implementation of national education policies. In Nigeria, where educational challenges are pronounced, the influence of educational management on policy-making is indispensable. This article critically examines how educational management contributes to shaping national education policies in Nigeria, the challenges faced, and the opportunities for improvement. It highlights the essential role of educational managers in policy formulation, implementation, and evaluation, while also offering recommendations for strengthening the synergy between educational management and policy processes to ensure improved educational outcomes.
Keywords: Educational Management, National Education Policies